Efektifitas Fermentasi Pupuk Kandang pada Hasil Panen Kentang Hitam (Plectranthus rotundifolius) di Daerah Dataran Rendah - Ngadiani Ngadiani; Vivin Andriani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
In order to realize food self-sufficiency, it is necessary to develop food alternatives other than rice, black potato plants are suitable as an alternative to be developed. Black potatoes have a high carbohydrate content, besides that they contain calcium, iron, and phosphorus. This study aims to determine the fermentation treatment of cow, goat, and chicken manure on black potato yields. This study used a factorial RAK (Randomized Block Design) with 3 factors and 3 replications. Factors for giving cow manure (S), goat manure (K), and chicken manure (A), each with 3 levels, namely 5 kg/plot, 10 kg/plot, and 15 kg/plot (S1, S2 , S3, K1, K2, K3, A1, A2, A3), negative control and NPK. The variable observed was yield, including: number of tubers, tuber weight, and black potato tuber diameter. The results showed that there was an effect of fermenting manure on black potato yields for 90 HST. Application of chicken manure with a concentration of 15 kg/plot gave better results in fermenting cow and goat manure. The number of tubers was 62 tubers, the tuber weight was 260 grams, and the tuber diameter was 2.12 mm.